2022
DOI: 10.3389/fneur.2022.1008717
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin E level and functional prognosis after traumatic brain injury with intracranial injury: A multicenter prospective study

Abstract: BackgroundTraumatic brain injury (TBI) is a major public health problem with high mortality and disability. Vitamin E, one of the antioxidants for treatment of TBI, has not been sufficiently evaluated for predicting prognosis of TBI. This study aimed to evaluate the prognostic value of vitamin E on functional outcomes of TBI patients with intracranial injury.MethodsA multi-center prospective cohort study was conducted in five university hospitals between 2018 and 2020. Adult TBI patients who visited the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“… 6 7 ‘A multicenter prospective study involving traumatic brain injury showed that the low serum vitamin E level was associated with unfavorable outcome at 1 and 6 months after the injury. 59 They emphasized that vitamin E is a potent antioxidant that administration of this drug resulted in a significant reduction in mortality and improved function outcome. A recent experimental study showed rapid delivery of a potent antioxidant that could decrease neuronal cell death, minimize the levels of ROS, and improve neurologic sequelae following SAH.…”
Section: Discussionmentioning
confidence: 99%
“… 6 7 ‘A multicenter prospective study involving traumatic brain injury showed that the low serum vitamin E level was associated with unfavorable outcome at 1 and 6 months after the injury. 59 They emphasized that vitamin E is a potent antioxidant that administration of this drug resulted in a significant reduction in mortality and improved function outcome. A recent experimental study showed rapid delivery of a potent antioxidant that could decrease neuronal cell death, minimize the levels of ROS, and improve neurologic sequelae following SAH.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was also evidenced in our experiment indicating poor neurological outcomes after ICH due to a high oxidative stress environment. Accumulated research evidence indicates a direct relationship between high ROS/oxidative stress in plasma/serum and poor neurological outcome/mortality after traumatic brain injury ( Nayak et al, 2008 ; Hohl et al, 2012 ; Lorente et al, 2019 ; Park et al, 2022 ). Maintaining antioxidant levels can effectively control the oxidative stress that induces damage and therefore, improve the neurological outcome ( Park et al, 2022 ), as is also observed after ZLHXTY capsule treatment after ICH in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…21 A multicenter, prospective cohort study showed that lower levels of Vitamin E correlate with poor neurological outcomes in TBI patients. 22 A clinical trial showed a lower mortality rate in patients who received vitamin E (400 IU/day intramuscular for 7 days) after severe TBI. 21 A retrospective study showed that the serum levels of vitamin D were low in TBI patients at the time of hospital admission, and supplementation of vitamin D significantly improved long-term performance, better Glasgow Outcome Scale (GOS) score, and ameliorated cognitive dysfunction.…”
Section: Nutraceuticalsmentioning
confidence: 99%